A risk index for COVID-19 severity is associated with COVID-19 mortality in New York City - Wil Lieberman-Cribbin; Naomi Alpert; Raja Flores; Emanuela Taioli (BMC, 2021)
Abstract Background New York City (NYC) was the epicenter of the COVID-19 pandemic, and is home to underserved populations with higher prevalence of chronic conditions that put them in danger of more serious infection. Little is known about how the presence of chronic risk factors correlates with mortality at the population level. Here we determine the relationship between these factors and COVD-19 mortality in NYC. Methods A cross-sectional study of mortality data obtained from the NYC Coronavirus data repository (03/02/2020-07/06/2020) and the prevalence of neighborhood-level risk factors for COVID-19 severity was performed. A risk index was created based on the CDC criteria for risk of severe illness and complications from COVID-19, and stepwise linear regression was implemented to predict the COVID-19 mortality rate across NYC zip code tabulation areas (ZCTAs) utilizing the risk index, median age, socioeconomic status index, and the racial and Hispanic composition at the ZCTA-level as predictors. Results The COVID-19 death rate per 100,000 persons significantly decreased with the increasing proportion of white residents (βadj = − 0.91, SE = 0.31, p = 0.0037), while the increasing proportion of Hispanic residents (βadj = 0.90, SE = 0.38, p = 0.0200), median age (βadj = 3.45, SE = 1.74, p = 0.0489), and COVID-19 severity risk index (βadj = 5.84, SE = 0.82, p <  0.001) were statistically significantly positively associated with death rates. Conclusions Disparities in COVID-19 mortality exist across NYC and these vulnerable areas require increased attention, including repeated and widespread testing, to minimize the threat of serious illness and mortality.